La razón como contexto de descubrimiento en la filosofía de Kant: libertad y finalidad. 2 - Lafuente, María Isabel (Revista Historia de la Educación Latinoamericana, 2004)
This second article, of reason as a context of discovery in Kant's philosophy, is a careful study of the notion of idea as a privileged term within that context. In this connection, an examination is made concerning the ways in which an idea may be produced, as well as the problems of their existence and necessity. There are also two notions examined here (World (as a mathematical totality) and Nature (as a dynamic totality)) in terms of which every idea can be thought of in a transcendental form. The dynamic direction is privileged and, therewith, the need to pay special attention to the notions of freedom and finality as concepts, implied in every invention.